Applying the Consolidated Framework for Implementation Research (CFIR) to examine barriers and facilitators to built environment change in five Canadian municipalities: Lessons from road safety and injury prevention professionals. (December 2022) - McCullogh, Emily; Giles, Audrey; Macpherson, Alison; Hagel, Brent; Buchan, Claire; Pike, Ian; Torres, Juan; Fuselli, Pamela; Pitt, Tona; Tavakolfar, Pegah; Desrochers, Élie; Richmond, Sarah A.
Abstract: Introduction: Road traffic injury and death continue to be a concern in Canada. The built environment (BE) is a contributing factor affecting the health of road users, yet there are significant challenges to making injury-reducing BE changes. This research increases our knowledge of these challenges by investigating the opinions of injury prevention and road safety professionals working in Canada about the barriers and facilitators to BE change. Methods: Semi-structured interviews and virtual focus groups (VFG) were conducted with 80 key informants (KIs) working in transport and injury prevention sectors in five Canadian cities: Vancouver, Calgary, Peel Region, Toronto, and Montréal. The Consolidated Framework for Implementation Research (CFIR) informed the interview guides. Thematic analysis was used to systematically analyze the data, a process that involved developing codes aligning with the research question, what are the barriers and facilitators to BE change? Themes were cross-referenced with the CFIR domains and constructs to illustrate how barriers and facilitators influence implementation of BE changes. Results: The prioritization of motor vehicles, lack of funding and resources, lack of political will, and sectoral silos were described as the most significant barriers to BE change. Cross-sectoral collaboration, data sharing, and champions and advocates were the most significant facilitators. Conclusions: Cross-referencing themes with the CFIR situated our findings within the scope of implementation science, which demonstrated how barriers and facilitators influence BE change project implementation. The prioritization of motor vehicles results in disproportionate injury and health risks for VRUs. Collaboration across sectors, with the support of champions and advocates, can facilitate sharing of resources, data, and expertise, which results in more opportunities to enact BE change. Knowledge of these barriers and facilitators, contextualized by the CFIR, makes a case for policy/decision-makers in Canada to approve BE projects that reduce risk of road traffic injury and death. Highlights: Motor vehicle prioritization is a barrier to BE change that influences decision-makers and the allocation of funding. Sectoral silos hinder BE change because they limit collaboration among those working towards the same road safety goals. Cross-sectoral collaboration facilitates sharing data and resources effectively implement road safety interventions. Mapping results onto the CFIR illustrates how barriers and facilitators influence BE change project implementation.